Protozoal infections of the cornea and conjunctiva in dogs associated with chronic ocular surface disease and topical immunosuppression. (3rd June 2015) - Beckwith‐Cohen, Billie; Gasper, David J.; Bentley, Ellison; Gittelman, Howard; Ellis, Angela E.; Snowden, Karen F.; Shock, Barbara C.; Yabsley, Michael J.; Dubielzig, Richard R.
Abstract: Objective: To describe five cases of protozoal keratitis or conjunctivitis in dogs with chronic preexisting ocular surface disease treated with long‐term immunosuppression. Animals studied: Five dogs that developed corneal or conjunctival mass lesions. Procedures: The database of the Comparative Ocular Pathology Laboratory of Wisconsin was searched for canine cases diagnosed with corneal or conjunctival protozoal infection. Five cases were identified, and tissues were examined using routine and special histochemical stains: immunohistochemical labels for Neospora caninum, Toxoplasma gondii, and Leishmania spp., and tissue sample PCR for Leishmania spp., Trypanosoma cruzi, tissue coccidia (i.e., T. gondii/Sarcocystis/Neospora), piroplasms, trichomonads, and Acanthamoeba . Electron microscopy was performed for two cases, and serology for N. caninum and T. gondii was available for three cases. Results: Preexisting ocular diseases included keratoconjunctivitis sicca and pigmentary keratitis ( n = 4) and pyogranulomatous meibomian adenitis ( n = 1). All dogs were treated with tacrolimus or cyclosporine for at least 1.2 years. Dogs were presented with fleshy corneal or conjunctival masses that were clinically suspected to be neoplastic ( n = 4) or immune mediated ( n = 1). Histologic examination revealed granulomatous inflammation with intralesional protozoal organisms. Amoeba ( n = 2), T. gondii ( n = 2), or Leishmania mexicana ( n = 1) were identified using molecular techniques. Serological tests were negative. Conclusions: Protozoal keratitis and conjunctivitis without systemic involvement appears rare and may be associated with chronic preexisting ocular surface disease treated with long‐term immunosuppression. Based upon clinical appearance, lesions could be confused with neoplasia. This is the first report of amoebic keratoconjunctivitis in dogs and of L. mexicana in dogs in the United States.